An ultra high frequency 921 mhz array antenna for rfid reader - Mohd Hisyam, Mohd Ariff; Imran Saifullah, Ishak; Mohd Zamri, Ibrahim; Mohammad Fadhil, Abas; Rahimah, Jusoh; Shakib, Mohammed Nazmus; Waheb Abdul Jabbar, Shaif Abdullah; Razali, Muda (2021)
Radio frequency identification (RFID) : agriculture goods,electronic devices, manifold volumes of industrial productsfor position recording, distribution reports and location facilitation An ultra-high frequency, UHF (300 MHz - 3GHz) frequency band RFID reader antenna has proven to be better compared to low frequency, LF (30 KHz – 300 kHz) and high frequency, HF (3 MHz – 300 MHz) frequency bands as it offers excellent read range and reading rate This project aims to develop an efficient high-gain patch antenna array to comply with the Malaysian Standard Frequency set for UHF RFID ranging from 921 MHz to 923 MHz.